Language Politeness Badan Permusyawaratan Desa (BPD) Meetings in Buria Village West Seram Regency Maluku Province - Lana Latue; Romilda Arivina da Costa (Universitas Pattimura, 2026)
This research aims to describe language politeness that occurs in BPD meetings. Politeness in language revolves around faces. Where everyone has a face (positive and negative face), and that face must be maintained and people must not be put down. The conversation participants play the role of a speaker or listener, alternately which shows the role of language politeness in BPD meetings in seeing whether the form of greeting is polite or not through the role of turn taking. This research is descriptive qualitative research. The data source for this research is a conversation between the BPD chairman, BPD members, and Buria Village Staff. The technique used in collecting data uses recording techniques, recording techniques, the validity of the data is obtained through theoretical triangulation. Judging from the classification of conversation data from BPD Staff and Buria Village Staff, using the language politeness scale from Brown and Levinson, namely the speaker and hearer relative power scale (social status ranking scale between speaker and scale of choice, as well as switching turns of speech by taking over turns of speaking (taking over), continuing the speech partner's speech, and creating initiation or realization. The results of this research show two conclusions. First, compliance with the negative type of politeness includes expressing respect and giving an apology. Second, compliance with the type of positive politeness includes seeking agreement, making offers, giving reasons, avoiding disagreements, involving the speech partner.